Role of Q-switched ND:YAG laser in nevus of Ota: A study of 25 cases - Shivangi Sharma; Abhijeet Kumar Jha; Sambeet Kumar Mallik (Wolters Kluwer Medknow Publications, 2011)
Background: Nevus of Ota is common condition in Indian patients. The condition is more common in females, with a male-female ratio of 1:4.8. Aim : To evaluate long-term efficacy safety and stability of Q-switched ND:YAG laser in treatment of Nevus of Ota. Design: 6 month follow-up of patients of Nevus of Ota, treated with Q-switched ND:YAG laser Materials and Methods : Twenty-five patients of Nevus of Ota were treated with Q-switched ND:YAG laser for a period of 1 year and 9 months; patient had fitzpatricks skin type 4 and 5; detailed history, clinical examination, ophthalmoscopy, and otoscopy was done in all cases; clinical photographs were taken before and after the completion of treatments. Six-month follow-up was done after the last session. Response to treatment was graded based on physician's global assessment. Result : More than 70% improvement was seen in 15 patients (60%). Eight patients (32%) had moderate and two patients (8%) showed mild improvement.